Alpha methyl acyl CoA racemase deficiency: Diagnosis with isolated elevated liver enzymes - Gündüz, Mehmet; Ünal, Özlem; Küçükçongar-Yavaş, Aynur; Kasapkara, Çiğdem (The Turkish Journal of Pediatrics, 2019)
Alpha methy acyl CoA racemase (AMACR) deficiency is a rare autosomal recessive peroxisomal disorder characterized by cholestatic liver disease in the neonatal period, and variable neurologic symptoms affecting central and peripheral nervous systems in the following years. We report a Turkish patient who was diagnosed with AMACR deficiency with presentation of isolated elevated liver enzymes. The patient was referred for elevated liver enzymes when he was 10 months old. He had no cholestasis history in the neonatal period. Initially, an etiology could not be identified. Ultimately, the patient was diagnosed with AMACR deficiency with previously unreported p.Cys20Tyr (c.596G > A) homozygous pathogenic variant. At last visit, when he was 7.5 years old, his growth, development and neurologic examination were all normal. Biochemical analysis was normal except for mildly elevated AST levels. We suggest that checking VLCFA analysis may be useful in isolated elevated liver enzymes with unknown etiology.
Keywords: alpha methyl acyl-CoA racemase (AMACR) deficiency; bile acids; elevated liver enzymes; peroxisomal disorders